NEWSPAPERS PORTRAYAL OF MENTAL HEALTH IN CHINA: CONTENT ANALYSIS OF BEIJING TODAY AND SHENZHEN DAILY - Lokumannage, Amila (International Journal of Innovative Technologies in Social Science, 2023)
This paper analyzed the how Chinese newspapers portrayal of Mental health in China. The coverage of mental health in media is important as media, usually the main source of information, can familiarize the reader with the topic of mental health in terms of prevention, treatment, and rehabilitation. Objectives of this study were, identify the specific disorders were named in articles in selected newspapers? Understand the overall tone of the articles which were analyzed? Study the frequency of the articles related to mental health and mental illness in two selected newspapers in China? The researcher selected two daily newspapers in China, Beijing Today and Shenzhen Daily in the period between 2015 and 2019 as the population of this study.  A total of 397 articles was selected over five year period (2015- 2019) and using quantitative and qualitative methods of content analysis, the researcher came up with the findings that suggest that Shenzhen Daily newspaper lack professionalism in their reporting and contribute to already existing stigmatization of mental illness in China. Beijing Today newspaper only somewhat contribute to overall stigmatization of mental illness in China- only low 8% of all articles examined in Beijing Today newspaper showed to have stigmatizing overall tone.